THE IMPORTANDE OF THE QUALITY MANAGEMENT SYSTEM FOR THE IMPLEMENTATION OF HACCP: a case study in a food company - Navarro, Jhulia Taina; Casagrande, Diego José (Revista Interface Tecnológica, 2025)
The study addresses the relevance of the Quality Management System (QMS) in the implementation of Hazard Analysis and Critical Control Points (HACCP) in a food company, focusing on the sausage segment. The QMS provides an organizational and process structure that facilitates the application of HACCP, an essential tool to ensure food safety and compliance with current legislation. The research highlights the importance of a well-structured QMS to ensure the effectiveness of HACCP. The study methodology combines a literature review and a practical case study, analyzing how a food company manages the safety of its products through these tools. The results indicate that the integration of the QMS with HACCP not only improves product safety, but also increases consumer confidence, guarantees quality and reduces operational costs, avoiding rework and product recalls.